PELAKSANAAN UJI KOMPETENSI KEAHLIAN REKAYASA PERANGKAT LUNAK PADA SMK NEGERI 1 TRIMURJO - Sita Muharni; M. Adie Syaputra (LPPM Universitas Bina Bangsa, 2023)
Expertise Competency Test (UKK) is an assessment held specifically for SMK students to measure student competency achievement equivalent to level 2 (two) or 3 (three) qualifications in the IQF. The Expertise Competency Test is carried out at the end of the study period by a Professional Certification Agency or an accredited educational unit together with business/industry partners. The results of the Expertise Competency Test for students will be an indicator of the achievement of graduate competency standards. Whereas for stakeholders the results of the Expertise Competency Test are used as a source of information on the competencies of prospective workers. The Software Engineering Expertise Program (RPL) is one of the competency skills in the field of computer technology and informatics that specifically studies computer programming. The implementation of the Skills Competency Test for the 2022/2023 school year at Trimurjo 1 State Vocational School is carried out face-to-face. The distance between the STMIK Dharma Wacana campus and SMK Negeri 1 Trimurjo is 9.9 KM and can be reached in 22 minutes. Community service activities through the Skills Competency Test program at Trimurjo 1 State Vocational School located on Jalan ABRI Liman Benawi Trimurjo Central Lampung with the expertise in Software Engineering are carried out for 2 (two) days, namely face to face. The number of competency test participants is 23 (twenty-three) people. In carrying out the Expertise Competency Test, participants are asked to sign proof of attendance on the attendance sheet provided. The community service method is through an expertise competency test program, namely in the form of assistance as an external examiner and has the authority to provide assessments to competency test participants in the field of Software Engineering expertise. Implementation of the Skills Competency Test which is one of the community service activities at Trimurjo 1 State Vocational School with a total of 23 (twenty-three) students in the field of Software Engineering expertise can be concluded that the results of the implementation of the Skills Competency Test are obtained with the criteria of scores based on 30% Aspects of Knowledge and 70% Aspects of Skills. Overall, the average student gets a score above 80 with a quality value of